The Effect of Digitization on the Safe Management of Anticoagulants - Austin, Jodie A.; Barras, Michael A.; Woods, Leanna S.; Sullivan, Clair M. (Applied Clinical Informatics, 2022)
Background Anticoagulants are high-risk medications and are a common cause of adverse events of hospitalized inpatients. The incidence of adverse events involving anticoagulants has remained relatively unchanged over the past two decades, suggesting that novel approaches are required to address this persistent issue. Electronic medication management systems (eMMSs) offer strategies to help reduce medication incidents and adverse drug events, yet poor system design can introduce new error types.Objective Our objective was to evaluate the effect of the introduction of an electronic medical record (EMR) on the quality and safety of therapeutic anticoagulation management.Methods A retrospective, observational pre-/poststudy was conducted, analyzing real-world data across five hospital sites in a single health service. Four metrics were compared 1-year pre- and 1-year post-EMR implementation. They included clinician-reported medication incidents, toxic pathology results, hospital-acquired bleeding complications (HACs), and rate of heparin-induced thrombocytopenia. Further subanalyses of patients experiencing HACs in the post-EMR period identified key opportunities for intervention to maximize safety and quality of anticoagulation within an eMMS.Results A significant reduction in HACs was observed in the post-EMR implementation period (mean [standard deviation [SD]] =12.1 [4.4]/month vs. mean [SD] = 7.8 [3.5]/month; p = 0.01). The categorization of potential EMR design enhancements found that new automated clinical decision support or improved pathology result integration would be suitable to mitigate future HACs in an eMMS. There was no significant difference in the mean monthly clinician-reported incident rates for anticoagulants or the rate of toxic pathology results in the pre- versus post-EMR implementation period. A 62.5% reduction in the cases of heparin-induced thrombocytopenia was observed in the post-EMR implementation period.Conclusion The implementation of an EMR improves clinical care outcomes for patients receiving anticoagulation. System design plays a significant role in mitigating the risks associated with anticoagulants and consideration must be given to optimizing eMMSs.
Keywords: anticoagulation; electronic health records; clinical decision support system; medication management; digital platforms; patient care; clinical error types; clinical analytics tools; electronic medication management systems